Identification of Autoreactive B Cell Subpopulations in Peripheral Blood of Autoimmune Patients With Pemphigus Vulgaris - Pollmann, Robert; Walter, Elias; Schmidt, Thomas; Waschke, Jens; Hertl, Michael; Möbs, Christian; Eming, Rüdiger (Frontiers in Immunology, 2019)
Pemphigus vulgaris (PV) is a rare blistering disease caused by IgG autoantibodies against the epidermal adhesion molecules desmoglein (Dsg)3 and Dsg1 providing a well-characterized paradigm of an antibody-mediated organ-specific autoimmune disease. In PV patients who have achieved clinical remission after B cell-depleting therapy, relapses often coincide with a reoccurrence of B cells and Dsg-specific autoantibodies. Here, we analyzed Dsg3-specific B cell subpopulations (i.e., total CD19+ B cells, CD19+CD27−B cells, CD19+CD27+ memory B cells, and CD19+CD27hiCD38hi plasmablasts) in peripheral blood of both PV patients (n = 14) at different stages of disease and healthy individuals (n = 14) by flow cytometry using fluorescently labeled recombinant human Dsg3 protein. Applying this approach, Dsg3-specific B cells could be detected at low frequencies (0.11–0.53% of CD19+ B cells) and numbers of Dsg3-specific memory B cells were significantly increased in PV patients in clinical remission receiving minimal immunosuppressive therapy. Finally, we confirmed in vitro that Dsg3-reactive memory B cells were able to produce anti-Dsg3 IgG autoantibodies upon ex vivo activation. Thus, monitoring of Dsg3-specific B cells in PV is of particular interest to further characterize the immunopathogenesis of PV.